Heroes of the valley - Stroud, Jonathan (London : Corgi Books, 2010)
Halli Sveinsson, a mischievous young man who does not fit in with his peers and siblings, plays a trick on Ragnor that goes too far, forcing him to embark on a hero's quest in which he will face highway robbers, monsters, an intriguing girl, and truths about his family and the legends he grew up with.
5.6
5-8.
5-8
Keywords: Heroes -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Fantasy; Heroes -- Fiction; Quests (Expeditions) -- Fiction; Heroes and heroines -- Fiction; Quests (Expeditions) -- Fiction; Fantastic fiction; Fantastic fiction